Evaluating occupational exposures of dental nurses: A retrospective study - Yuan, Hongmei; Shi, Rui; Chen, Wenwen; Ma, Ying; Liu, Zhiqing; Liu, Fan; Yang, Jingmei (Frontiers in Public Health, 2022)
Objective: To investigate occupational blood-borne pathogen exposure among dental nurses and their attitudes towards infected patients, as well as the effectiveness of the training course, to provide a scientific basis for improving the quality of safety management in dental hospital. Materials and Methods: The study was conducted using questionnaires administered from November 2019 to December 2019 in three hospitals in Sichuan Province, China. Frequencies for answers were calculated and presented as percentages. Results: In total, 257 valid questionnaires were returned. Most (61.9%) nurses stated that they were involved in occupational exposure. Among them, 154 had experienced sharp injuries, and the syringe needle was the most common instrument for injuries (45.8%). Twenty-two individuals had mucosal exposure, and the proportion of eye exposure was the highest (90.9%). Only associations between training and mucosal membrane exposure were found; however, the relevance was weak (r = 0.141). Of the participants, 86.4% felt morally responsible for taking care of patients with infectious diseases, and most (92.6%) said they would continue with this career. Conclusions: Occupational exposure, particularly to sharp injuries, was common in medical care among dental nurses; however, vocational training had little effect on their incidence. As dental nurses still have positive attitudes towards patients with infectious diseases, more effective training should be conducted.